Factors Related to Sexual Behavior Among Teenager Dating in Denpasar City - I Gusti Ngurah Edi Putra; Putu Erma Pradnyani; Ni Nyoman Astri Artini; Ni Luh Eka Purni Astiti (Faculty of Public Health, Andalas University, 2017)
The earlier age for dating among teenagers has an impact to increase the chance of sexual behavior. This study aimed to identify the factors related to sexual behavior among teenager dating in Denpasar City. This study was observational analytic with cross-sectional approach. Sample size was 880 students dating with sampling technique using nonprobability sampling. This study showed the proportion of teenager who had risky sexual behavior was 22,1%. Factors related to risky sexual behavior among teenager dating were aged >15 years old (OR=3,0; 95%CI=1,9-4,8; p<0,001), male (OR=3,0; 95%CI=2,2-4,2; p<0,001), education level of senior high school compared to junior high school (OR=3,9; 95%CI =2,4-6,2; p<0,001), education level of vocational high school compared to junior high school (OR=2,4; 95%CI =1,5-3,9; p=0,001), private school (OR=2,2; 95%CI=1,6-3,1; p<0,001), never accessed to health reproductive information (OR=2,0; 95%CI =1,3-3,0; p=0,001), accessed to pornography content (OR=4,1; 95%CI=2,8-6,1; p<0,001), lack of knowledge (OR=1,7; 95%CI=1,2-2,4; p=0,006), and lack of attitude (OR=3,1; 95%CI=2,2-4,5; p<0,001). There were relationship between age, sex, educational level, school status, the access of health reproductive information, the access to pornography content, knowledge, and attitude toward risky sexual behavior. Giving information comprehensively regarding reproductive and sexual health is essential approach through involving active participation from parents and teachers.